Tax incentives on income as a determinant of the Effective Tax Rate - Moisés Geraldo Cavalcante Macaíba Costa de Sousa; Rômulo Benício Lucena Filho; Robério Dantas de França (Revista Contabilidade & Finanças, 2025)
Abstract The article analyzes the effectiveness of tax incentives in determining the Effective Tax Rate (ETR) of Brazilian companies, addressing a gap in the literature that does not adequately consider the effects of these incentives on profit. Based on a sample composed of 392 publicly traded companies listed on B3, the research analyzed data collected from 2013 to 2022, totaling 3,920 observations. Various ETR metrics were used, including Generally Accepted Accounting Principles (GAAP), Current, Deferred, Cash, Cash3, and Sectoral. The applied methodology analyzed the data through descriptive statistics and panel regression models of unbalanced data, aiming to understand the relationships between tax incentives and ETR, as well as the impact of variables such as size, leverage, capital intensity, inventory intensity, and profitability. The results revealed significant variations in ETR metrics, highlighting a complex relationship between tax incentives and tax behavior. Interestingly, in metrics such as ETR Cash and Cash3, the increase in tax incentives was associated with a higher tax burden. Other metrics, such as GAAP ETR and Current ETR, also revealed substantial differences, highlighting the influence of specific factors from the economic sector and the regulatory environment. The study recognizes limitations, such as the dependence on accounting data and the absence of detail on specific types of incentives. It is recommended that future research explore more detailed sectoral analyses and consider changes in Brazilian legislation. These conclusions provide significant contributions to the understanding of corporate tax strategies, offering relevant subsidies for public policy makers, companies, and investors interested in the transparency and competitiveness of the corporate environment.